Anterior and posterior parts of the rat ventral tegmental area and the rostromedial tegmental nucleus receive topographically distinct afferents from the lateral habenular complex. Issue 10 (9th April 2017) - Petzel, Anja; Bernard, René; Poller, Wolfram C.; Veh, Rüdiger W.
Abstract: That activation of the reward system involves increased activity of dopaminergic (DA) neurons in the ventral tegmental area (VTA) is widely accepted. In contrast, the lateral habenular complex (LHb), which is known as the center of the anti‐reward system, directly and indirectly inhibits DA neurons in the VTA. The VTA, however, is not a homogenous entity. Instead, it displays major functional differences between its anterior (aVTA) and posterior (pVTA) regions. It is not precisely known, whether habenular input to the aVTA, pVTA, and the newly recognized rostromedial tegmental nucleus (RMTg) are similarly or differently organized. Consequently, the present investigation addressed the connections between LHb and aVTA, pVTA, and RMTg using retrograde and anterograde tracing techniques in the rat. Our experiments disclosed strictly reciprocal and conspicuously focal interconnections between LHbM (LHbMPc/LHbMC) and PN, as well as between RLi and LHbLO. In addition, we found that LHb inputs to the aVTA are dorsoventrally ordered. Dorsal parts of the aVTA receive afferents from LHbL and LHbM, whereas ventral parts of the aVTA are preferentially targeted by the LHbM. LHb afferents to the pVTA are distinct from those to the RMTg, given that the RMTg is primarily innervated from the LHbL, whereas pVTA receives afferents from LHbM and LHbL. These data indicate the existence of two separate pathways from the LHb to the VTA, a direct and an indirect one, which may subserve distinct biological functions. Abstract : The study employs retrograde and anterograde tract tracing techniques to analyze the projections of the medial (LHbM) and lateral (LHbL) divisions of the lateral habenular complex (LHb), the center of the anti‐reward system, to the anterior (aVTA) and posterior (pVTA) parts of the VTA and the rostromedial tegmental nucleus (RMTg).